Ransom slavery along the Ottoman borders : early fifteenth-early eighteenth centuries - Dávid, Géza; Fodor, Pál (Ottoman Empire and its heritage, 2007)
The volume is an ambitious attempt to give a comprehensive picture of trade in captives along the European borders of the Ottoman Empire, especially in Central Europe. It brings together a great deal of so far unpublished archival material and thus integrates a new area into the research.